Oral and Parenteral vs. Parenteral Antibiotic Prophylaxis for Patients Undergoing Laparoscopic Colorectal Resection: An Intervention Review with Meta-Analysis - Giuseppe Sangiorgio; Marco Vacante; Francesco Basile; Antonio Biondi (MDPI AG, 2021)
This study aims to systematically assess the efficacy of parenteral and oral antibiotic prophylaxis compared to parenteral-only prophylaxis for the prevention of surgical site infection (SSI) in patients undergoing laparoscopic surgery for colorectal cancer resection. Published and unpublished randomized clinical trials comparing the use of oral and parenteral prophylactic antibiotics vs. parenteral-only antibiotics in patients undergoing laparoscopic colorectal surgery were collected searching electronic databases (MEDLINE, CENTRAL, EMBASE, SCIENCE CITATION INDEX EXPANDED) without limits of date, language, or any other search filter. The outcomes included SSIs and other infectious and noninfectious postoperative complications. Risk of bias was assessed using the Cochrane revised tool for assessing risk of bias in randomized trials (RoB 2). A total of six studies involving 2252 patients were finally included, with 1126 cases in the oral and parenteral group and 1126 cases in the parenteral-only group. Meta-analysis results showed a statistically significant reduction of SSIs (OR 0.54, 95% CI 0.40 to 0.72; p < 0.0001) and anastomotic leakage (OR 0.55, 95% CI 0.33 to 0.91; p = 0.02) in the group of patients receiving oral antibiotics in addition to intravenous (IV) antibiotics compared to IV alone. Our meta-analysis shows that a combination of oral antibiotics and intravenous antibiotics significantly lowers the incidence of SSI compared with intravenous antibiotics alone.